International ENGOs in China: a Significant Presence and a Fast-Changing Reality - Volpe, Marco (Sinología hispánica. China Studies Review, 2018)
Received: Revised: Accepted: Sinologia Hispanica, China Studies Review, 5, 2 (2017), pp. 113-148 September 2017 November 2017 Devember 2017 The paper examines the impact that international ENGOs have had on Chinese environment situation and the implication of the Law of People’s Republic of China on the Administration of the Activities of Overseas Nongovernmental Organisations in Mainland China. Based on the review of historical profile of NGOs and their enhanced role within the international politics, the paper analyzes China’s leadership evolutionary behaviour in international climate change conferences and investigates the international ENGOs’ current status, strategies and projects in China. The paper argues that international ENGOs have had a positive, even if limited, impact in protecting Chinese environment and in supporting Chinese civil society to emerge and strengthening the public participation and awareness. It also argues that, the implementation of the new law certainly puts international NGOs under higher scrutiny; however, further implications are, to date, only partially predictable.